PATHOLOGY OF OESOPHAGOSTOMIASIS IN THE GOAT - Kumar, Rajesh; Gupta, VK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Oesophagostomiasis is an important parasitic disease of goat caused by Oesophagostomum columbianum. Burdens of only a few hundred worms are associated with anorexia, diarrhea and ill thrift, resulting in poor growth of the animal. Pimply gut alone accounts for 3.16% intestinal condemnation (Kusiluka et al., 1995).